1989
DOI: 10.1002/hed.2880110502
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of some prognostic factors in small squamous cell carcinoma of the mobile tongue: A multicenter study in Sweden

Abstract: In a retrospective study of 58 patients from all over Sweden, treated for small squamous cell carcinoma of the mobile tongue (T1N0M0), different prognostic factors were evaluated. A partial glossectomy was performed as primary treatment in all patients. The cancer recurred in 28 (38%) of 58 patients. One of 7 patients with only local recurrence, and 9 of 14 with recurrence in the neck died of their disease. The relative survival rate was 77%. Of the prognostic factors tested, tumor thickness was found to be th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(45 citation statements)
references
References 21 publications
2
43
0
Order By: Relevance
“…It has been reported earlier in a study consisting of 95 patients with primary neck nodes treated with RT and neck dissection that 26% recurred in the regional neck nodes during the follow-up period (24). In a Swedish study of early Stage I tongue cancers treated with surgery of the primary tumor 14 of 58 patients had recurrences in the neck region with a mean follow-up time of 33 months (25). In another study among early tongue carcinoma patients, the recurrence rate after elective neck dissection vs. observation was 9% and 47%, respectively (17).…”
Section: Discussionmentioning
confidence: 89%
“…It has been reported earlier in a study consisting of 95 patients with primary neck nodes treated with RT and neck dissection that 26% recurred in the regional neck nodes during the follow-up period (24). In a Swedish study of early Stage I tongue cancers treated with surgery of the primary tumor 14 of 58 patients had recurrences in the neck region with a mean follow-up time of 33 months (25). In another study among early tongue carcinoma patients, the recurrence rate after elective neck dissection vs. observation was 9% and 47%, respectively (17).…”
Section: Discussionmentioning
confidence: 89%
“…Although most authors substantially agree that tumor thickness is a significant parameter for predicting nodal metastasis development and for survival, the cutoff thickness is really quite variable, ranging from 1.5 mm 24 to 10 mm. 64,75 It is unclear why the studies have reached such inconsistent results with reference to the cutoff measurement point. A possible explanation could be related to the different measurement techniques and methods that were adopted, as discussed previously.…”
Section: Resultsmentioning
confidence: 96%
“…Most of these patients were treated with excision alone, and did not receive any electrive irradiation or neck dissection, and Nathanson et al (9) found a recurrence rate of 38% in another Swedish study of TINO tumours treated with excision, and several authors have shown a high percentage of conversion from NO to N + even for TI tumours (16).…”
Section: Discussionmentioning
confidence: 99%